The iPLA2γ is identified as the membrane potential sensitive phospholipase in liver mitochondria. Issue 18 (20th July 2015) - Rauckhorst, Adam J.; Pfeiffer, Douglas R.; Broekemeier, Kimberly M.
Abstract : Previous reports from our lab identified a mitochondrial calcium‐independent phospholipase A2 activity that is activated when the mitochondrial membrane potential is decreased. This activity was demonstrated to influence occurrence of the permeability transition. Originally, this activity was ascribed to the iPLA2 β protein. Recently, both iPLA2 β and iPLA2 γ knock out mice have been generated. It has been shown by others that the iPLA2 γ plays a significant role in progression of the permeability transition. In this paper, using the iPLA2 β and iPLA2 γ knock out mice we show that the membrane potential sensitive activity is the iPLA2 γ. Abstract : R‐BEL inhibits the Δψ sensitive iPLA2 activity in rat liver mitochondria. Mouse mitochondria contain a Δψ sensitive iPLA2 activity that is inhibited by BEL. iPLA2 β knockout animals have activity similar to wild type in the presence of CCCP. A substantial decrease in Δψ sensitive activity was observed in iPLA2 γ KO animals. The iPLA2 isozyme responsible for Δψ sensitive iPLA2 activity is the iPLA2 γ.